Higher Order Thinking Skills on Writing Tasks in The English Textbook Entitled "My Next Word": Keterampilan Berpikir Tingkat Tinggi pada Buku Teks Bahasa Inggris yang Berjudul "My Next Word" (Bilingua, 2024)
The aims of this research are to know the composition and dominant cognitive domain of higher-order thinking skill based on Bloom’s Taxonomy in writing task and of the English textbook “My Next Word” for the sixth-grade of elementary school. The result of the research shows that the higher order thinking skill is higher than the lower order thinking skill. It is proven by the results that shows the distribution of higher order thinking level obtains 31 out of 37 instructions or 83,8 %. Meanwhile, the lower order thinking level obtains 6 out of 37 instruction or 16,2%. Furthermore, as the focus of this research, the distribution of higher order thinking skill in the English textbook My Next Word shows that the create level get the highest distribution by obtaining 17 out of 37 instructions, while the evaluate level get the second position by obtaining 9 out of 37 instructions, and the analysis skill get the third position by obtaining 5 out of 37 instructions. It can be concluded that the dominant level of higher order thinking skill in writing tasks in the English textbook My Next Word is create level. It also shows that there is imbalance portion of the higher order thinking skill in writing tasks.